2013
DOI: 10.1309/ajcps6ow6dynognh
|View full text |Cite
|
Sign up to set email alerts
|

Activated Partial Thromboplastin Time and Anti-Xa Measurements in Heparin Monitoring

Abstract: We examined the concordance of heparin levels measured by a chromogenic anti-Xa assay and the activated partial thromboplastin time (APTT) during unfractionated heparin therapy (UFH) and the biochemical basis for differences between these measures. We also investigated the endogenous thrombin potential (ETP) as a possible measure of anticoagulation. Paired measures of anti-Xa and APTT were performed on 569 samples from 149 patients on UFH. The anti-Xa values and the APTT were concordant in only 54% of measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 15 publications
4
72
0
2
Order By: Relevance
“…Consequently, it demonstrates that the anti‐FXa level may provide a more accurate assessment of anticoagulation. This observation agrees well with the suggestion to preferably use an anti‐FXa test and not a PT or aPTT test to evaluate anticoagulation 40, 45. The percentage of FXa inhibition has a relatively small inter‐individual variability because the anti‐Xa assay is directly based on enzymatic inhibition, which can be accurately measured using well‐defined chemical reagents that are not biologically derived.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consequently, it demonstrates that the anti‐FXa level may provide a more accurate assessment of anticoagulation. This observation agrees well with the suggestion to preferably use an anti‐FXa test and not a PT or aPTT test to evaluate anticoagulation 40, 45. The percentage of FXa inhibition has a relatively small inter‐individual variability because the anti‐Xa assay is directly based on enzymatic inhibition, which can be accurately measured using well‐defined chemical reagents that are not biologically derived.…”
Section: Discussionsupporting
confidence: 86%
“…For apixaban, however, the model is overpredicting the actual observed aPTT values (see Figure 3 d ). A possible reason might be the difference in thromboplastin reagent concentrations used in the rivaroxaban and apixaban clinical trials 40. Consequently, this may hamper the prediction of coagulation effects of different compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that differences in the concentrations of several coagulation proteins (especially factor VIII) in patient plasma samples may explain this variability. 17 A number of hospitals, including our own, use the aPTT to monitor DTIs administered by continuous infusion. Given the questions raised about the use of the aPTT to monitor unfractionated heparin, there is reason to question whether a different method of monitoring parenteral DTIs should be used.…”
Section: Discussionmentioning
confidence: 99%
“…The ACT correlates poorly with the heparin dose. 33 Therefore, some centers use an anti-factor Xa level or aPTT to manage heparin. Whole blood assays including thromboelastography (TEG) and thromboelastometry (ROTEM) are used by some centers, but further studies to standardize these techniques are required.…”
Section: Ecmo Antithrombotic Therapymentioning
confidence: 99%